STRATEGI KOMUNIKASI ORGANISASI DALAM PROSES PEMBERDAYAAN EKONOMI (The Commercium, 2022)
Abstract Malang is one of the regencies with the highest rank of migrant worker placements in East Java and even occupied the national level. Seeing this condition, SBMI is here to fight for the protection of PMI there. That is not only about the law but also the economy that is the main focus at this time. Through a coordination system in the form of organizational communication strategies, Malang Regency DPC has succeeded in building its economic empowerment. For example, in physical form, namely SBMI Mart. Therefore, researchers are interested in knowing more about Organizational Communication Strategy in the Process of Economic Empowerment with a case study of DPC SBMI Malang Regency. This research uses a case study method with a qualitative approach. Through the interview and observation process, the results show that the strategies used are inculcating historical values, establishing SBMI Mart, identifying audiences, simple messages, and flexibility in message distribution. Theoretically and practically, this research can be used as a basis for both further research and other stakeholders to raise awareness about the potential development of migrant workers in the future. Keywords: Organizational Communication Strategy, Economic Empowerment, SBMI